Perforation of thin plain and stiffened CFRP panels - Found, M. S. (Animo Repository, 2002)
Static indentation and impact tests have been performed on thin plain and stiffened CFRP panels. The impact perforation threshold level may be estimated from the work done by the indentor during a static indentation test. Normalised damage maps produced from impact test data suggest that both plain and stiffened panels have similar damage profiles. A means of predicting the behaviour of large panels based on laboratory test data is suggested.